Construction and characterization of nano iron complex ionophore for electrochemical determination of Fe(III) in pure and various real water samples. (11th September 2019) - Ali, Tamer Awad; Mahmoud, Walaa H.; Mohamed, Gehad G.
Abstract : Electrochemical methods represent an important class of widely used techniques for the detection of metal ions. The unique chemical and physical properties of nanoparticles make them extremely suitable for designing new and improved sensing devices, especially electrochemical sensors and biosensors. This study focused on the synthesis of a nano‐Fe(III)–Sud complex and its characterization using various spectroscopic and analytical tools, optimized using the density functional theory method, screened for antibacterial activity and evaluated for possible binding to DNA using molecular docking study. Proceeding from the collected information, nano‐Fe(III)–Sud was used further for constructing carbon paste and screen‐printed ion‐selective electrodes. The proposed sensors were successfully applied for the determination of Fe(III) ions in various real and environmental water samples. Some texture analyses of the electrode surface were conducted using atomic force microscopy. At optimum values of various conditions, the proposed electrodes responded towards Fe(III) ions linearly in the range 2.5 × 10 −9 –1 × 10 −2 and 1.0 × 10 −8 –1 × 10 −2  M with slope of 19.73 ± 0.82 and 18.57 ± 0.32 mV decade −1 of Fe(III) ion concentration and detection limit of 2.5 × 10 −9 and 1.0 × 10 −8  M for Fe(III)–Sud‐SPE (electrode I) and Fe(III)–Sud‐CPE (electrode II), respectively. The electrode response is independent of pH in the range 2.0–7.0 and 2.5–7.0, with a fast response time (4 and 7 s) at 25°C for electrode I and electrode II, respectively. Moreover, the electrodes also showed high selectivity and long lifetime (more than 6 and 3 months for electrode I and electrode II, respectively). The electrodes showed good selectivity for Fe(III) ions among a wide variety of metal ions. The results obtained compared well with those obtained using atomic absorption spectrometry. Abstract : Novel nano iron complex is synthesized and characterized using different spectroscopic, analytical and textural tools. The formed complex was used as ionophore for development of new CPE and SPE for determining Fe(III) in pure form and in different real water samples. The modified electrodes have many advantages including ease of preparation, Nernstian behavior, low cost, Low toxicity, good reproducibility and wide dynamic range.